Zdravljenje bolečine pri revmatoidnem artritisu - Kolarič, Barbara (Farmacevtski vestnik, 2012)
Rheumatoid arthritis (RA) is an inflammatory disorder. Its most aggravating symtom is pain. The role of immunomodulators in RA therapy is to mitigate inflammation, thus reducing or eliminating pain in affected joints. Most people with RA are faced with frequent or ongoing pain. There are various types of pain caused by RA: nociceptive, neuropathic and psychogenic. Most people with rheumatoid arthritis will experience all of these types of pain. Better understanding of chronic pain management strategies, effects of analgetics, noticing and reducing side effect risks in time, enables significant pain relief and improvement of patient's quality of life.
Keywords: Arthritis, Rheumatoid; Bolečina; Klinična farmakologija; Pain; Pharmacology, Clinical; Revmatoidni artritis; Therapy; Zdravljenje